2011
DOI: 10.2139/ssrn.1839243
|View full text |Cite
|
Sign up to set email alerts
|

How Far Do Children Move? Spatial Distances after Leaving the Parental Home

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Place attachment and belonging are consistently reported as important (Glendinning et al, ; Kloep, Hendry, Glendinning, Ingebrigtsen, & Espnes, ; Leopold, Geissler, & Pink, ; Looker & Naylor, ; Thissen, Droogleever Fortuijn, Strijker, & Haartsen, ) and can out‐weigh any perceived negatives to staying in the rural. Attachment may be because of family roots, memories, and a sense of home; to social factors, such as close family or friendship ties and a sense of community; to places of living memory, residential familiarisation, or socialisation; or to the physical and natural qualities of the area (aesthetic, wilderness, and biological diversity; Gustafason, ; Lewicka, ; Rérat, ; Trell, van Hoven, & Huigen, ).…”
Section: Towards a Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Place attachment and belonging are consistently reported as important (Glendinning et al, ; Kloep, Hendry, Glendinning, Ingebrigtsen, & Espnes, ; Leopold, Geissler, & Pink, ; Looker & Naylor, ; Thissen, Droogleever Fortuijn, Strijker, & Haartsen, ) and can out‐weigh any perceived negatives to staying in the rural. Attachment may be because of family roots, memories, and a sense of home; to social factors, such as close family or friendship ties and a sense of community; to places of living memory, residential familiarisation, or socialisation; or to the physical and natural qualities of the area (aesthetic, wilderness, and biological diversity; Gustafason, ; Lewicka, ; Rérat, ; Trell, van Hoven, & Huigen, ).…”
Section: Towards a Conceptual Frameworkmentioning
confidence: 99%
“…Thus far, we have identified the importance of life events, relationships with others, and the ongoing nature of the staying process. A further factor emerges, that of "place" (Barcus & Brunn, 2010;Leopold et al, 2012;Rérat, 2014;Roin, 2015). Place, however, is particularly nuanced in the staying process and includes familial, physical, and social elements that represent strong senses of belonging.…”
Section: Staying As An Attachment To (Rural) Placementioning
confidence: 99%
“…In Sweden, moves toward neighborhoods with extended kin are more likely for people with less education and lower incomes or who are out of work (Hedman, 2013). In Germany, children leaving home typically relocate nearby, but move farther away if they leave a high-income household in an urban area, move out early, are better educated, or have no children (Leopold, Geissler, & Pink, 2012).…”
Section: Background On Kin and Spatial Distancementioning
confidence: 99%
“…Thus, selection out of coresidence and into independent living may downwardly bias estimates of the association between relationship quality and residential distance. Time spent in the parental home during young adulthood has been linked to increased solidarity later (Leopold et al., 2012), a finding with likely implications for subsequent relocations. To take account of this potential selection bias, analyses of residential proximity need to consider coresidence.…”
Section: Background On Kin and Spatial Distancementioning
confidence: 99%
“…Prior studies of the United States and other countries that examined proximity beyond coresidence found that adults with lower education were more likely to live close to their parents and other family members (Chan & Ermisch, , ; H. Choi, Schoeni, Langa, & Heisler, ; Clark & Wolf, ; Compton & Pollak, ; Garasky, ; Kalmijn, ; Lauterbach & Pillemer, ; Leopold, Geissler, & Pink, ; Malmberg & Pettersson, ; Rogerson, Weng, & Lin, ; Spring et al, ). There also were differences in proximity to parents by race, with Blacks living closer to their parents than Whites (Bianchi, McGarry, & Seltzer, ; Compton & Pollak, ; Spring et al, ).…”
Section: Prior Studiesmentioning
confidence: 99%